Coexisting pathology of ectopic pregnancy and dermoid cyst: An uncommon occurrence - Ramraje, Sushma; Giri, Sulagna; D’Costa, Grace; Sengupta, Abhishek (Indian Journal of Case Reports, 2018)
Mature cystic teratomas (dermoid cysts) are common benign ovarian neoplasms. About 10% of dermoid cysts are detected duringpregnancy. Multiple gynecologic pathologies occurring together are uncommon, and both an ectopic pregnancy and dermoid cystare seen concurrently being unknown and poorly documented. Here, we report a case of ectopic pregnancy and dermoid cystoccurring simultaneously in a 30-year-old woman.